Study on human emotion based on facial expressions through human machine communication - Murshed, Tahmin Aysha; Dastider, Prantar (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2020.